Techno‐Economic Analysis of Additively‐Manufactured Wind Turbine Blade Tips That Enable Technology Integration - Brent C. Houchens; Evan G. Sproul; Jonathan C. Berg; Paolo G. Caserta; Miguel H. Hernandez; Daniel R. Houck; Helio Lopez; David C. Maniaci; Graham Monroe; Joshua A. Paquette; Sal Rodriguez; Julia N. Tilles; et al. (Wind Energy)
ABSTRACT The Additively‐Manufactured, System‐Integrated Tip (AMSIT) project is leveraging the flexibility of 3D printing to integrate several technologies in a wind turbine blade tip, while reducing the levelized cost of electricity (LCOE) produced. The design integration is demonstrated for a 200‐kW–scale turbine with 13‐m blades, with the outer 15% of the blade replaced with a 3D‐printed design. Aerodynamic performance is enhanced without increasing swept area through inclusion of a winglet and surface texturing, both challenging for traditional manufacturing. Longevity and durability are improved through integrated lightning and leading edge erosion protection. Increased power, reduced repair frequency, and ease of repair through blade modularity all contribute to reduced LCOE. The analysis is also extended to modern MW‐scale designs to estimate the impact of the technology at scale, demonstrating the potential to reduce LCOE significantly for modern onshore turbines, with even higher potential savings offshore.